Chitosan–chondroitin sulphate nanoparticles for controlled delivery of platelet lysates in bone regenerative medicine - Santo, Vitor E. (2012)
In this work a new formulation of nanoparticles (NPs) based on the electrostatic interaction between chitosan and chondroitin sulfate (CH/CS NPs) is proposed for the controlled release of proteins and growth factors (GFs), specifically Platelet Lysates (PLs). These nanoparticulate carriers are particularly promising for protein entrapment because the interactions between the polysaccharides and the entrapped proteins mimic the interactions between chondroitin sulfate and proteins in the native extracellular matrix. Spherical non-cytotoxic NPs were successfully produced, exhibiting high encapsulation efficiency for physiological levels of GFs and a controlled protein release profile for longer than one month. Moreover, it was also observed that these NPs can be uptaken by human adipose derived stem cells (hASCs), depending on the concentration of NPs in the culture medium and incubation time. This shows the versatility of the developed NPs, which besides acting as a protein delivery system, can also be used in the future as intracellular carriers for bioactive agents such as nucleotides. The release of PLs from CH/CS NPs also proved to be effective for enhancement of in vitro osteogenic differentiation of hASCs, as shown by the increased levels of mineralization, suggesting not only the effective role of the delivery system but also the role of PLs as an osteogenic supplement for bone tissue engineering and regenerative medicine applications.